Discovery of modulators for the PD-1/PD-L1 interaction by molecular simulation and bioassay. (23rd September 2021) - Li, Guangping; Guo, Haiqiong; Zhao, Linan; Feng, Huixian; He, Huawei; Chen, Yan; Wang, Yuanqiang; Lin, Zhihua
Abstract : PD-1-targeted discovery of modulators by virtual screening, molecular docking, surface plasmon resonance binding assay and T-cell activation assay. Abstract : The combination of human programmed cell death protein 1 (hPD-1) and its ligand hPD-L1 activates the immune escape of tumors, and the blockage in the PD-1/PD-L1 involved pathway can enhance the endogenous anti-tumor immunity. Therefore, blocking the interaction of PD-1 and its ligand PD-L1 has become a promising cancer immunotherapy technique. Recently, different types of small molecules and peptides have been discovered as PD-1/PD-L1 inhibitors. In the present work, in silico virtual screening and biomolecular interaction analysis (BIAcore) against our internal peptide library are used to discover peptides as probes to inhibit the binding between PD-1 and PD-L1. Particularly, RRQWFW-NH2 and RRWWRR-NH2 are found to have better docking scores of 7.69 and 8.34, respectively. Sequentially, molecular dynamics (MD) simulations and surface plasmon resonance (SPR) are used to further validate our predictions. Interestingly, our results showed that RRQWFW-NH2 and RRWWRR-NH2 show moderate activity to inhibit the protein–protein interaction between PD-1 and PD-L1, in which the experimental data are consistent with the computational data. Our research provides a robust computational method for the development of new PD-1/PD-L1 inhibitors and provides some new candidate peptide drugs for cancer immunotherapy.